The association of essential dietary trace elements and their mixture with cognition: a prospective study - Li, Huihui; Yin, Zhongmin; Cui, Fusheng; Wang, Weijing; Zhang, Dongfeng (Frontiers in Nutrition, 2025)
BackgroundThe association of dietary essential trace elements (ETEs) and their mixture with cognition remains unclear.MethodsProspective cohort data on the association between dietary ETEs [e.g., iron (Fe), copper (Cu), zinc (Zn), manganese (Mn), selenium (Se), and iodine (I)] and general cognition were obtained from the UK Biobank (UKB) database. Linear regression and restricted cubic splines (RCS) were used to examine the association between individual dietary ETEs and general cognition, including the identification of the inflection points. The Bayesian kernel machine regression (BKMR) model was applied to analyze the association between a mixture of six ETEs and general cognition, as well as potential interactions among ETEs. Stratified analysis and sensitivity analysis were also conducted.ResultsSignificant non-linear association between individual dietary ETEs and general cognition was observed, with the inflection points for the various elements being as follows: Fe: 15 mg/day, Zn: 10 mg/day, Cu: 1.5 mg/day, I: 250 μg/day, Mn: 5 mg/day, and Se: 45 μg/day. The BKMR analysis showed an inverted “U”-shaped association between dietary ETE mixture and general cognition, with Fe and Zn playing major roles. Dietary Mn was the major contributor in males, while Zn was predominant in females. In the hypertensive population, dietary Zn and Mn play major roles.ConclusionThere are non-linear associations between dietary Fe, Zn, Cu, I, Mn, Se—as well as their mixture—and general cognition. Among these, Fe and Zn play major roles within this mixture. In addition, there are sex differences in the main contributing ETE, with Mn in males and Zn in females.